Enhanced proton conduction in zirconium phosphate/ionic liquids materials for high-temperature fuel cells. (22nd January 2021) - Mohammed, Hanin; Al-Othman, Amani; Nancarrow, Paul; Elsayed, Yehya; Tawalbeh, Muhammad
Abstract: This work reports the synthesis of high temperature proton conductors based on zirconium phosphate and imidazolium-based ionic liquids. This material is evaluated for high temperature proton exchange membrane fuel cells applications operating at 200 °C. The characterization results show high proton conductivity, enhanced water uptake properties, changes in structure, and exfoliation in zirconium phosphates crystal layers upon the introduction of the ionic liquid. The proton conductivity results demonstrate that there is an optimum amount of ionic liquid that can be introduced into zirconium phosphates to enhance its conductivity beyond which, the conductivity starts to decrease. At the optimum conditions, the addition of ionic liquids enhances the proton conductivity of the zirconium phosphates material by orders of magnitude. The results show a high proton conductivity the order of 10 −2 S cm −1 at room temperature and high anhydrous proton conductivity of 10 −4 S cm −1 at 200 °C. These findings indicate that the zirconium phosphate-ionic liquid material has a great potential as solid proton conductors for fuel cells applications operating at elevated temperatures. Graphical abstract: Image 1 Highlights: Enhanced proton conduction in modified ZrP/ionic liquids materials is reported. High anhydrous proton conductivity at 200 °C is described. Intercalation followed by exfoliation are observed in the modified material.